2022
DOI: 10.1186/s12885-022-09991-6
|View full text |Cite
|
Sign up to set email alerts
|

The impact of a breast cancer educational intervention in Ghanaian high schools

Abstract: Introduction Globally breast cancer is the leading cause of cancer with an estimated 2.3 million new cases and 685,000 deaths in 2020. Late presentation is the hallmark of breast cancer in Ghana for which ignorance and fear are the major reasons fuelled largely by myths and misconceptions. Breast cancer awareness and education needs to start early to bring about a change in knowledge, attitude and practices. However, Breast cancer awareness activities in Ghana have usually targeted adult women.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 26 publications
2
2
0
1
Order By: Relevance
“…Consistent with these results, several studies indicate that adolescents possess limited knowledge about breast cancer risk factors and symptoms. 4,22,23 The results of this study demonstrate that the educational intervention significantly increased adolescent knowledge about breast cancer risk factors and symptoms, aligning with the results of studies conducted in other countries. 4,[23][24][25][26] Similar to our results, the study by Al-Hosni et al 24 found that the educational program increased adolescents' knowledge about breast cancer risk factors and symptoms.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Consistent with these results, several studies indicate that adolescents possess limited knowledge about breast cancer risk factors and symptoms. 4,22,23 The results of this study demonstrate that the educational intervention significantly increased adolescent knowledge about breast cancer risk factors and symptoms, aligning with the results of studies conducted in other countries. 4,[23][24][25][26] Similar to our results, the study by Al-Hosni et al 24 found that the educational program increased adolescents' knowledge about breast cancer risk factors and symptoms.…”
Section: Discussionsupporting
confidence: 86%
“…4,22,23 The results of this study demonstrate that the educational intervention significantly increased adolescent knowledge about breast cancer risk factors and symptoms, aligning with the results of studies conducted in other countries. 4,[23][24][25][26] Similar to our results, the study by Al-Hosni et al 24 found that the educational program increased adolescents' knowledge about breast cancer risk factors and symptoms. In a study conducted in two high schools, the knowledge level of adolescents about breast cancer risk factors increased from 33% to 55%, and the knowledge level regarding these risk factors rose from 55.0% to 79.0%.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Setelah 3 bulan didapatkan bahwa pengetahuan umum tentang kanker payudara pada pra-pendidikan (29,1%) meningkat menjadi 72,5% (p<0,001), pengetahuan tentang tanda dan gejala meningkat dari 33,1% menjadi 55% (p<0,001), pengetahuan tentang faktor risiko meningkat dari 55,3% menjadi 79,2% (p<0,001), dan pengetahuan tentang pemeriksaan dan skrining payudara meningkat dari 9,8% menjadi 22,2% (p<0,001), dan kinerja siswa secara keseluruhan meningkat dari 17,2% menjadi 59,4% (p<0,001). Intervensi edukasi dan pembagian leaflet untuk dibawa pulang oleh para siswi efektif dalam meningkatkan dan mempertahankan ingatan tentang kanker payudara tentang pengetahuan umum kanker payudara, faktor risiko, tanda dan gejala, serta pemeriksaan payudara sendiri (24).…”
Section: Media Leafletunclassified
“…15 , 16 To achieve this, first, a thorough understanding of the barriers to accessing breast cancer early detection and diagnostic services is required. In Ghana, several barriers have been cited, including lack of community knowledge and misconceptions of breast cancer to allow for early recognition, 17 , 18 perceived and actual costs associated with seeking care, 19 , 20 and distance required to travel to access available services, 21 , 22 among others. Currently, geographic availability and access to breast cancer early diagnostic services in Ghana are not well defined.…”
Section: Introductionmentioning
confidence: 99%